Spermatogenesis in the parasitoid Diachasmimorpha longicaudata (Hymenoptera: Braconidae) - Carabajal Paladino, Leonale Suzel (2017)
The study of spermatogenesis in Hymenoptera is limited to few taxa due to limitations to access the material in the right stage for analysis. The information available up to now states that the gametogenesis in males involves a modified meiosis, similar to mitosis. This is due to the haplodiploid sex determination system present in the order, where females are diploid and males are haploid. In the present work, we examined the spermatogenesis process in the parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae). We performed squash preparations from testes of individuals from the third larval instar until the adult stage. Some cytological traits, such as the presence of a monopolar spindle, were analysed in detail by means of histological semi-thin sections. The spermatogenesis in this species comprises an abortive first division with the formation of an anucleated cytoplasmic bud and a nucleated cell, and an equal second division of the nucleated cell, leading to the generation of two mature spermatozoa. The results presented herein provide more information about the process of spermatogenesis in Hymenoptera, which has not been studied in depth in parasitic species.